Constitutive modelling of the 6061 aluminium alloy under hot rolling conditions and large strain ranges. (May 2020) - Rudnytskyj, André; Simon, Peter; Jech, Martin; Gachot, Carsten
Abstract: Constitutive models were built based on the results of isothermal hot compression tests for a 6061 aluminium alloy at temperatures of 400, 450, 500, and 550 °C and strain rates of 0.1, 1, and 10 s −1, which reproduced conditions of the hot rolling forming process for this alloy. The Garofalo-Arrhenius, Johnson-Cook, and Hensel-Spittel material models, modified versions of the latter two, as well as a newly proposed Johnson-Cook model were applied based on the experimental data. The predictive power of the constitutive models was assessed for a wide range of plastic strains, from the start of the plastic region up to a strain value of 1, including strain hardening at the beginning of the flow curve. Comparisons between experiments and models by means of the Pearson correlation coefficient and relative errors, considering different strain ranges, showed that the goodness of the models depends strongly on the considered strain range. Results revealed that the Garofalo-Arrhenius model provided the highest accuracy at any strain range, followed by the Hensel-Spittel models and the newly proposed Johnson-Cook model, which performed more accurately than its commonly employed modified version. Graphical Abstract: Unlabelled Image Highlights: Constitutive models were constructed based on hot compression tests for the 6061 aluminium alloy. Strain hardening and strains up to 1 were accurately represented by certain models. A new Johnson-Cook model was more accurate than its popular modified version. Garofalo-Arrhenius was the most accurate model in different strain ranges.